Structural Relationships Modeling of Neuroticism, Openness, and Mental Health with the Mediating Role of Social Support among Students - Naghizadeh, Maryam; Mirzaian, Bahram; Heidari, Shaban (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The present study aimed to model the structural relationships between personality traits (neuroticism and openness) and mental health with the mediating role of social support among students.Methods and Materials: The research method was fundamental in terms of purpose and correlational in terms of method, specifically using structural equation modeling. The statistical population included all students of Islamic Azad University, Sari branch, in the 2023-2024 academic year, totaling 5,400 individuals. Using Kline's method and a non-random (available) sampling method, 269 individuals were selected as the sample. After explaining the research by the investigator and obtaining the respondents' willingness to participate, the NEO Five-Factor Inventory (NEO-FFI) (McCrae & Costa, 1992), the 28-item General Health Questionnaire (GHQ-28) (Goldberg, 1972), and the Perceived Social Support Questionnaire (Zimet, 1988) were administered. For data analysis, both descriptive (dispersion index, central tendency index, mean, and standard deviation, data normalization) and inferential (structural equations) statistical methods were used.Findings: The results showed that the two personality traits of neuroticism and openness have a direct effect on mental health. Additionally, the personality traits of openness and neuroticism have an indirect effect on mental health through the mediation of social support. Furthermore, the findings indicated that 59% of mental health can be explained by personality traits and social support in direct and indirect pathways (R² = 0.59). Specifically, the personality trait of neuroticism has a 31% direct effect on mental health, and neuroticism with the mediation of social support has a 37% indirect effect on mental health among students. The findings also showed that 12% of mental health can be explained by the variables of neuroticism and social support in direct and indirect pathways (R² = 0.12). Additionally, the results indicated that the personality trait of openness has a 15% direct effect on mental health, and openness with the mediation of social support has a 26% indirect effect on mental health among students. The findings further suggested that 3% of mental health can be explained by the variables of extraversion and social support in direct and indirect pathways (R² = 0.03).Conclusion: The results indicated that the personality traits of neuroticism and openness have a significant direct effect on mental health; and that these traits, through the mediating role of social support, have an indirect effect on mental health.